(untitled) (Bangladesh Journal of Pharmacology, 2016)
The present study evaluated the antiproliferative and apoptotic effect of quinine on oral cancer cells Hep-2 and KB. Cell inhibition, apoptosis and anti-inflammatory effects were explored by nuclear DNA cleavage, condensation, change in membrane potential of mitochondria. Meanwhile, inflammatory and apoptosis-related mRNA and proteins expressions such as iNOS COX-2, IL-6, Bcl-2, mutant p53, Bax, caspase-3 and NF-?B were determined by RT-PCR and Western blotting assays. Results showed that, quinine treatment significantly inhibited the cell viability and colony formation, inhibited cell proliferation lead to increased generation of reactive oxygen species induction of MMP depolarization, morphological changes and DNA damage in dose- and time-dependent manner. Moreover, quinine significantly decreased the iNOS, COX-2, IL-6, Bcl-2 and mutant p53 simultaneously up-regulated Bax, caspase-3 expressions through the inhibition of NF-?B suggest that quinine may serve as a potential candidate in the prevention of cell proliferation and enhances apoptosis via inhibiting up-stream signalling. Video Clip of Methodology: Programmed cell death assay by dual staining: 17 min 25 sec Click to watch